INFLUENCE OF TRANSVERSE ROUGH TEXTURE TO LUBRICATION CHARACTERISTICS OF ROLLING BEARING - LU YaDi; Qi XiuMei; GAO ChuangKuan (Jixie qiangdu)
The surface roughness data of test-pieces with transverse profiles were firstly measured by a roughness profile measuring analyzer. With the help of the Fourier nonlinear approximation the measured data was used to form a roughness function which was superimposed to film thickness equation and a mixed thermal elastohydrodynamic lubrication model for the rolling bearing was then established. Based on the model,45 sets of numerical calculations were carried out by changing the roughness values under other conditions of the rolling bearing were fixed. Then the two quantitative relationships between the average oil film at the contact point and the roughness as well as the maximum subsurface principal stress and the roughness are respectively established through the regression analysis of the calculation results.